Short Note: The distribution of Trichaleurina javanica in Central Kalimantan (Indonesia) and its Ethnomycology: Catatan Singkat: Distribusi Trichaleurina javanica di Kalimantan Tengah (Indonesia) dan Etnomikologinya - Putra, Ivan; Gloris, Hari (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
The genus Trichaleurina is a member of Pezizales, which was previously rarely reported from Indonesia. Trichaleurina was first reported by Boedjin in 1932 and 1959 but still used the name Galiella javanica and Galiella celebica. Trichaleurina is closely related to Galiella, Sarcosoma, and Bulgaria. In Indonesia, the first report on T. javanica from West Java in 2020. In the following year, information about the distribution of Trichaleurina was reported from Central Kalimantan (Indonesia). The current study aimed to describe the specimens from Central Kalimantan based on morphological data and record the ethnomycological use by the local people. Fresh materials were used to describe the morphological features. The macrofungi lived on dead wood in solitarily manner, fruiting body round to oval, conical at the bottom, dark brown that gets darker at the base, ascus 8-spored, cylindrical in shape, spores 25-26 × 9-10μm, thick walled. Our specimen was identical to those reported from Bogor (West Java). Trichaleurina javanica is used as food in the daily life of the Dayak Maanyan Tribe in Tamiang Terbang, Central Kalimantan, Indonesia. They usually consumed this macrofungi as local soup. This information adds to the record of the diversity and potency of macrofungi in Indonesia.